2016
DOI: 10.3109/03009742.2016.1155644
|View full text |Cite
|
Sign up to set email alerts
|

Rasch analysis of the Norwegian version of the Arthritis Self-Efficacy Scale (ASES)

Abstract: The ASES had good fit to the Rasch model and correlations with other instrument scores that followed hypotheses, lending further support to the application of the instrument in patients with rheumatic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The Norwegian ASES‐11 is scored on a five‐point Likert scale ranging from 1 (very uncertain) to 5 (very certain). Scores are summarized for each scale, with higher scores representing a higher level of self‐efficacy (Garratt, Klokkerud, Lochting, & Hagen, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Norwegian ASES‐11 is scored on a five‐point Likert scale ranging from 1 (very uncertain) to 5 (very certain). Scores are summarized for each scale, with higher scores representing a higher level of self‐efficacy (Garratt, Klokkerud, Lochting, & Hagen, ).…”
Section: Resultsmentioning
confidence: 99%
“…ASES is widely used in research within rheumatology and is found to have acceptable internal consistency and construct validity in two systematic reviews, but there is a lack of research on responsiveness (Banerjee et al, ; Miles, Pincus, Carnes, Taylor, & Underwood, ). In this study, we applied a recently validated Norwegian version of the ASES‐11 with a five‐point descriptive scaling that has not yet been tested for responsiveness (Garratt et al, ). Although responsiveness of ASES‐11 in this study was poor, we recommend ASES‐11 as a questionnaire to be used in the evaluation of PE for patients with IA.…”
Section: Discussionmentioning
confidence: 99%
“…Self‐efficacy was measured by the subscales for pain and other symptoms from the Arthritis Self‐Efficacy Scale (ASES) , ranging from 0–100, with higher scores representing higher levels of self‐efficacy. The measurement properties of the Norwegian version of the ASES have recently been tested, with good results in patients with rheumatic diseases undergoing rehabilitation .…”
Section: Methodsmentioning
confidence: 99%
“…A revised version of the Arthritis Self-Efficacy Scale was used to measure self-efficacy to cope with pain (five items) and others symptoms (six items) [31,32]. In this scale, the respondent is asked about level of certainty in being able to undertake specific tasks (eg, decrease pain, continue daily activities, control fatigue, and do something to feel better).…”
Section: Emotions and Self-efficacymentioning
confidence: 99%